Assessment of Comparative Efficiency Based on Integral Index of Reforms: Evidence from Transcaucasian Republics - Samson Davoyan; Lusya Galoyan; Knarik Ayvazyan; Roza Kurghinyan (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
The main purpose of the research is to develop a new methodology, that will allow to create an Integral Index of Reforms, quantitatively assess various reforms that have been implemented for 2012-2017 in 66 countries of the world. In the article with the help of the Integral Index of Reforms, that contains 20 partial indexes, reforms in different areas have been measured. The Integral Index of Reforms was constructed based on principle component analysis; contribution of sub-indexes was defined through panel data regression. Based on this methodology various reforms have been assessed and analysed for 2012-2017 in three Transcaucasian Republics: Armenia, Georgia and Azerbaijan.
Keywords: E66; E61; F01; O10; 330; reform; comparative efficiency; integral index of reforms; Armenia; Georgia; Azerbaijan